Investigation of localized surface plasmon/grating-coupled surface plasmon enhanced photocurrent in TiO2 thin films - Nootchanat S. (Royal Society of Chemistry, 2014)
We fabricated plasmonic gold nanoparticle (AuNP)-TiO2 nanocomposite films and measured the photocurrent that originates from the water-splitting reaction catalyzed by the AuNP-TiO2 nanocomposite photoelectrocatalytic (PEC) electrode. The localized surface plasmon resonance (LSPR) of the gold nanoparticles affected the generation of photocurrent by TiO2 upon illumination with visible light. Electrochemical impedance spectroscopy (EIS) revealed that the improvement in the photocurrent generation originates from an enhancement in electron-hole pair generation induced by the SPR of the plasmonic gold nanoparticles rather than the extension of the electron lifetime. Moreover, we introduced a novel method to enhance the photocurrent of TiO2 by a multiple plasmonic effect, i.e., LSPR of plasmonic gold nanoparticles and the grating-coupled propagating SP on a gold grating. We fabricated the AuNP-TiO2 nanocomposites on a gold-coated Blu-ray disc recordable (BD-R). The enhancement of the photocurrent due to the combination of LSPR and the grating-coupled SP was investigated.